Intended and Unintended Targeting of Polymeric Nanocarriers: The Case of Modified Poly(glycerol adipate) Nanoparticles - Weiss, Verena M; Lucas, Henrike; Mueller, Thomas; Chytil, Petr; Etrych, Tomáš; Naolou, Toufik; Kressler, Jörg; Mäder, Karsten (Macromolecular bioscience, 2018)
Biodegradable nanoparticles based on stearic acid-modified poly(glycerol adipate) (PGAS) are promising carriers for drug delivery. In order to investigate the impact of the particle interface characteristics on the biological fate, PGAS nanoparticles are covalently and noncovalently coated with N-(2-hydroxypropyl) methacrylamide (HPMA) copolymers. HPMA copolymer-modified PGAS nanoparticles have similar particle sizes, but less negative zeta-potentials. Nanoparticles are double labeled with the fluorescent dyes DiR (noncovalently) and DYOMICS-676 (covalently bound to HPMA copolymer), and their biodistribution is investigated noninvasively by multispectral optical imaging. Both covalent and noncovalent coatings cause changes in the pharmacokinetics and biodistribution in healthy and tumor-bearing mice. In addition to the intended tumor accumulation, high signals of both fluorescent dyes are also observed in other organs, including liver, ovaries, adrenal glands, and bone. The unintended accumulation of nanocarriers needs further detailed and systematic investigations, especially with respect to the observed ovarian and adrenal gland accumulation.
Keywords: nosiče léků; fluorescenční barviva; Drug Carriers; Tissue Distribution; Xenograft Model Antitumor Assays; biologicky odbouratelné plasty; methakryláty; Biodegradable Plastics; Nanoparticles; Fluorescent Dyes; HT29 Cells; Methacrylates; Mice; polyestery; lékové transportní systémy; Neoplasms; nanoparticles; xenogenní modely - testy protinádorové aktivity; zvířata; tkáňová distribuce; Humans; ovaries; nádory; bones; nanočástice; Polyesters; biodegradable polymers; myši; Drug Delivery Systems; adrenals; buňky HT-29; lidé; Animals